2021
DOI: 10.3390/soilsystems5030042
|View full text |Cite
|
Sign up to set email alerts
|

A Contribution to Soil Fertility Assessment for Arid and Semi-Arid Lands

Abstract: Soil fertility must be viewed as a dynamic concept that involves the constant cycling of nutrients between organic and inorganic forms. In this context, it refers also to supply adequate amounts of water and aeration for plant growth. Soil fertility under arid and semi-arid lands is constrained not only by limited water availability but also by small organic matter contents. Most fertility assessment systems are based on organic matter contents as the main parameter. However, crop experiments from various irri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Therefore, low soil fertility has negatively affected plant growth and biodiversity in arid soils [20]. Because of the existence of subtle environmental conditions, which were not taken into account by the soil fertility assessment systems developed by researchers and scientists for temperate and humid areas, Hag Husein et al [21] concluded that the conventional systems have a low potential for adoption in arid areas. Therefore, soil fertility assessment tools tailored to arid areas should be developed to ensure widespread adoption and actual application.…”
Section: Scarcity Of Watermentioning
confidence: 99%
“…Therefore, low soil fertility has negatively affected plant growth and biodiversity in arid soils [20]. Because of the existence of subtle environmental conditions, which were not taken into account by the soil fertility assessment systems developed by researchers and scientists for temperate and humid areas, Hag Husein et al [21] concluded that the conventional systems have a low potential for adoption in arid areas. Therefore, soil fertility assessment tools tailored to arid areas should be developed to ensure widespread adoption and actual application.…”
Section: Scarcity Of Watermentioning
confidence: 99%
“…Soil fertility in arid and semi-arid conditions is limited by environmental extremes of hot and cold temperatures, as well as low water availability (33). The agro-climatic parameters present constraining characteristics for agriculture, especially in the North of the bassin (Korhogo, Ferkessedougou and Boundiali) which sometimes experiences severe droughts and the centre of Mankono with less severe climatic conditions (11).…”
Section: Evaluation Of Limiting Soil Propertiesmentioning
confidence: 99%
“…Maize (Zea mays L.) ranks the third staple crop after wheat and rice with an annual 0.27 million tons of production from 0.14 million hectares of plantation in Afghanistan [7,8], where most soil characterizes as high pH, low organic matter and moisture, low N and P availability under a semiarid and arid climate [9,10]. Mainly due to lack of chemical fertilizer supply plus a high price and poor field management, the averaged maize yield is quite low as 1.93 -2.20 t ha -1 in Afghanistan compared to 5.88 t ha -1 globally [7 -10].…”
Section: Introductionmentioning
confidence: 99%